Use of episcleral cyclosporine implants in dogs with keratoconjunctivitis sicca: pilot study. (5th May 2014) - Barachetti, Laura; Rampazzo, Antonella; Mortellaro, Carlo M.; Scevola, Stefania; Gilger, Brian C.
Abstract: Purpose: To describe the use, tolerability, and efficacy of episcleral silicone matrix cyclosporine (ESMC) implants in dogs with keratoconjunctivitis sicca (KCS). Methods: Retrospective study. ESMC implants (1.9 cm length, 30% wt/wt CsA in silicone; with approximately 12 mg of CsA loaded into them) were used in dogs with KCS responsive to topical CsA (good candidate, GC) or not responsive (poor candidate, PC). Ocular surface inflammation scores, Schirmer tear test (STT) values, and ocular discharge quantity were evaluated and compared. Results: Twenty‐seven eyes (15 dogs) received an ESMC implant for KCS; 15 eyes were considered GC, and 12 were considered PC. Both GC eyes and PC eyes showed a significant increase in STT values (increase of 7.7 and 8.5 mm/min; P  = 0.023 and P  = 0.003, respectively) after placement of ESMC implants (mean follow‐up 18 ± 2 and 10.4 ± 15 months, respectively). Clinical signs improved significantly in both groups during the same follow‐up, with reduction in conjunctival hyperemia ( P  < 0.001), corneal neovascularization ( P  = 0.004), corneal opacity ( P  = 0.003), and ocular discharge ( P  = 0.002). ESMC implants were well tolerated by all dogs, but two eyes lost the device at 12‐months and 1‐week follow‐up, respectively. Conclusions: Results from this study suggest that the EMSC implants were well tolerated and efficacious in dogs with KCS responsive to topical CsA as well as dogs with poor response to topical therapy. Further study is needed to determine the duration of efficacy and optimal dose of CsA.